1997
DOI: 10.1063/1.118885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zr/Ti ratios on the deformation in the hysteresis loop of Pb(Zr,Ti)O3 thin film capacitors

Abstract: Electric field shift and deformation in the polarization-electric field characteristics of Pb(Zr,Ti)O3 (PZT) thin film capacitors with various Zr/Ti ratios have been studied as a function of the annealing temperature after patterning the top sputter-deposited Pt electrode using reactive ion etch with Ar gas. A large field shift and a constriction in the hysteresis loops are observed, particularly in low Zr/Ti PZT films annealed below 400 °C. A strong blocking layer effect in unannealed capacitor is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The argument regarding ion milling damage as the cause of the reduction of , P r , and P s is plausible, since ion milling has been reported to induce space charge in the near surface region that shields the electric field applied and inhibits domain wall motion. [20][21][22] To elucidate this concern, a test heterostructure consisting of MgO/LSCO/PLZT was fabricated, milled for 0, 3, and 5 min, and subjected to ferroelectric and dielectric testing. The values after ion milling were found to be equivalent to those prior to milling once adjusted for a change in film thickness ͑data not shown͒, demonstrating that our milling conditions do not adversely affect the film properties.…”
Section: Resultsmentioning
confidence: 99%
“…The argument regarding ion milling damage as the cause of the reduction of , P r , and P s is plausible, since ion milling has been reported to induce space charge in the near surface region that shields the electric field applied and inhibits domain wall motion. [20][21][22] To elucidate this concern, a test heterostructure consisting of MgO/LSCO/PLZT was fabricated, milled for 0, 3, and 5 min, and subjected to ferroelectric and dielectric testing. The values after ion milling were found to be equivalent to those prior to milling once adjusted for a change in film thickness ͑data not shown͒, demonstrating that our milling conditions do not adversely affect the film properties.…”
Section: Resultsmentioning
confidence: 99%
“…17 A possible explanation is the non-ferroelectric passive layer such as air gap or a second phase at the top electrode interface formed by sputtering, and another possibility is that the internal field caused by trapped charges makes domain motions difficult. 25 C. Frequency and temperature dependence of dielectric properties…”
Section: B Piezoelectric and Ferroelectric Propertiesmentioning
confidence: 99%
“…16,[19][20][21][22][23]41 It is generally agreed that PZT thin films with compositions near the morphotropic phase boundary (x ϳ 0.53) exhibit higher dielectric constants than other compositions and that the coercive field increases with the Ti content (more tetragonal-like). Extensive electrical characterizations on films with a range of Zr/Ti ratios have shown that their properties, including dielectric constant, remanent polarization, coercive field, and pyroelectric coefficient, depend strongly on its B-site cation composition.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive electrical characterizations on films with a range of Zr/Ti ratios have shown that their properties, including dielectric constant, remanent polarization, coercive field, and pyroelectric coefficient, depend strongly on its B-site cation composition. 20,41 Recently, an increase of remanent polarization with increased Ti content from x 0.2-0.6 has been reported for sol-gel-derived PZT films after optimum annealing. The remanent polarization was shown by some groups to be the lowest when x approached the phase boundary, 16,22 whereas different "x dependence" of these properties had also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation